Tumor-associated antigens as possible targets for immune therapy in head and neck cancer: comparative mRNA expression analysis of RAGE and GAGE genes - Götte, Karl; Riedel, Frank; Hörmann, Karl; Schadendorf, Dirk; Eichmüller, Stefan B. (Acta oto-laryngologica, 2002)
Specific immune therapy targeting residual areas of cancer cells may emerge as a powerful treatment strategy for head and neck squamous cell carcinoma (HNSCC). In order to define possible targets for immune therapy, we evaluated the frequency of two groups of tumor antigens - the RAGE and GAGE families - by means of reverse transcriptase polymerase chain reaction using primary HNSCCs ( n =28), mucosa specimens as normal controls ( n =10) and HNSCC cell lines ( n =6). By means of specific primer selection we could differentiate between RAGE-1, -2, -3 and-4, as well as between two groups of GAGE genes (GAGE-1,2,7 vs GAGE-3,4,5,6,8). While all mucosa tissues (from smokers and non-smokers) were negative for both antigen families, 24/28 investigated tumors were positive for up to 5 tumor antigens. Among the RAGE genes, RAGE-1-positive tumors were the most abundant (8/28), followed by RAGE-2 (7/28) and RAGE-4 (6/28). Differences in the locations of HNSCCs were reflected by different RAGE family members being expressed most frequently: larynx, RAGE-1; oropharynx, RAGE-2; and hypopharynx, RAGE-4. Primers against GAGE-1,2,7 and GAGE-3,4,5,6,8 revealed 6/27 and 16/27 positive tumors, respectively. This report suggests that RAGE genes and GAGE-3,4,5,6,8 may be promising candidates for specific immune therapy in HNSCC.